2005
DOI: 10.1111/j.1460-9592.2004.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relatively low dose of oral transmucosal ketamine premedication in children: a comparison with oral midazolam

Abstract: These results indicate that a relatively low dose of oral transmucosal ketamine premedication provides no benefits over oral midazolam in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Ketamine is a dissociative anesthetic and analgesic that is also used as a sedative drug, maintaining the patient’s muscle tone and the respiratory system’s protective reflexes (29,31). However, in adults, ketamine may also cause hallucinations and nightmares during the recovery period, and as such it sees limited use in adults; these side effects are rarely seen in children (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketamine is a dissociative anesthetic and analgesic that is also used as a sedative drug, maintaining the patient’s muscle tone and the respiratory system’s protective reflexes (29,31). However, in adults, ketamine may also cause hallucinations and nightmares during the recovery period, and as such it sees limited use in adults; these side effects are rarely seen in children (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, in adults, ketamine may also cause hallucinations and nightmares during the recovery period, and as such it sees limited use in adults; these side effects are rarely seen in children (31). …”
Section: Discussionmentioning
confidence: 99%
“…Behaviour at anaesthetic induction, postoperative psychological morbidity and subsequent dental attendance were not found to differ between the premedication groups. more benefi cial effects, 22 Ko et al have shown 0.2 mg/kg to be effective in reducing emergence agitation and postoperative analgesic requirements. 23 Moreover, Erlandsson et al have reported this dose to be effective for conscious sedation of uncooperative paediatric dental patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration is associated with high hepatic first-pass effect; only 16% of a given dose is bioavailable [22]. Horiuchi et al [23] reported the use of transmucosal ketamine in the form of a lollipop containing 50 mg ketamine (48 ml ¼ 2400 mg ketamine in a candy base and 12 mg of atropine sulfate preparation divided into 48 equal lollipop pieces and refrigerated), but could not show any superiority over midazolam 0.5 mg/kg. Ketamine provides sedation by 20-25 min, and leads to calm separation and good induction.…”
Section: Ketaminementioning
confidence: 99%